Pteridophytes diversity in the summit region of Gunung Ledang, Johor, Malaysia - Shahruddin, Zulkefli (2019)
A study of pteridophytes diversity was conducted in Gunung Ledang, Johor which is the highest peak of the southern Peninsular Malaysia and gazette as Johor National Parks. It is a virgin forest undisturbed by human activities which consists of endemic plants found only in this mountain. Destruction of ecosystems and climate changes may cause extinction of species of pteridophytes in this mountain. Studies on pteridophytes flora and diversity in Gunung Ledang, Johor have been conducted several times but none was officially documented and published except for Ridley in 1901. Hence, this study was conducted to reveal the diversity of pteridophytes in summit region of Gunung Ledang, Johor after a gap of eleven decades. Several field works were carried out from November 2015 to January 2016, and five sampling plots sized 20m x 20m (400m2) were developed to study the diversity of pteridophytes based on cardinal direction (North, South, East, West) and at peak of the mountain. The number of individuals of each species in the plots was counted and their relative abundance was obtained from calculation. A total of 27 species from 16 families and 21 genera were identified and recorded. The largest family is Gleicheniaceae (four species) followed by Selaginellaceae and Pteridaceae (three species) respectively. The majority of the pteridophytes are terrestrial (85%) while the remaining 11% are epiphytic and 4% are litophytic. The highest density of pteridophytes collected in this study was Pteridium aquilinum while the highest frequency of pteridophytes was Dicranopteris linearis and Taenitis dimorpha with 60% population distribution. The diversity indices reveals that Plot C (West) has higher diversity of pteridophytes where Shannon’s index value was 1.84 and Simpson’s index value show of 0.80. In comparison with previous records, there are 16 species are new recorded in Gunung Ledang, including Taenitis dimorpha, which is endemic to Peninsular Malaysia. As this study reveals the 16 new records and an endemic species, it is essential for Gunung Ledang,Johor National Parks to systematically and comprehensively study its pteridophytes flora so that its diversity status can be ascertained.